Development and performance evaluation of okra planter - Sahoo, P K; Srivastava, A P (Journal of Agricultural Engineering, 2000)
A three-row ridger planter was developed for planting soaked okra seed on the ridges. The seed metering mechanism in the planter is of inclined plate type. Power is transmitted from ground wheel to metering system through chain and sprokets. The machine has four ridger bottoms with runner type furrow opener for making ridges. The seed is placed in these ridges at desired depth. The ridge size and depth of placement of seed are adjustable. The implement is operated by a 35 hp tractor. During evaluation the field capacity of the machine was found to be 0.2 ha/h with an average operating speed of 2.27 kmph. The field efficiency of the planter was found to be 66.5 per cent. There was a saving of 77 man hours per hectare by planting okra seed with planter as compared to making ridges with tractor drawn ridgers followed by manual planting. The cost of operation was found to be Rs. 810/- per hectare and a saving of 76% over manual planting was recorded. The crop parameters and yield were comparable in case of machine planting and manual planting.